حكم السفتجة في الفقه الإسلامي وتطبيقاتها المعاصرة The Rule of the Bill of Exchange in Islamic Jurisprudence and Contemporary Applications - عارف, عارف علي; ديرشوي, خالد زين العابدين; نورالدين, موفق عبد الحفيظ (Journal of Islam in Asia (E-ISSN 2289-8077), 2016)
الملخّص كانت السفتجة ولا تزال توفيراً للجهد والعناء، ورفعاً للضيق، فلولاها لاضُطر المدين إلى نقل مال الوفاء إلى بلـد الدائن، واضُطر الدائن إلى نقل المال إلى بلد المدين، وهذه تكاليف إضافية، الأصل توفيرها، طبقاً لتعاليم شرعنا الحنيف، وقد تكلم الفقهاء في حكمها؛ فأجازوها في حال عدم اشتراط المنفعة في العقد، أو إذا كانت منفعة السفتجة للمقرض والمقترض معاً، أو وجدت حالة ضرورة، أو كان المنفعة للمقترض وحده، ولكنهم اختلفوا في حكمها في حال اشتراط المنفعة في عقد القرض. وبعد عرض آراء الفقهاء في هذه المسألة، وبيان حجج كل رأي، رجَّحنا القول بجواز اشتراط منفعة السفتجة في القرض بشرط ألا يكون فيها ضرر على المدين أو المقترض، كما يمكننا القول أن كلاً من عملية التحويل المصرفي، والكمبيالة ما هي إلا صور مستحدثة من السفتجة في الفقه الإسلامي، وإن كان بينهما بعض الفوارق. وقد اتبعنا في بحثينا هذا المنهج التحليلي المقارن الذي يقوم على دراسة النصوص وتحليلها، ومناقشتها، مبينا صورها وتكييفها الفقهي على ضوء مذاهب الفقهاء وأدلتهم فيها. الكلمات المفتاحية: السفتجة، الدين، القرض، الكمبيالة، الحوالة، التحويلات المصرفية. Abstract The bill of exchange was introduced as a mechanism to facilitate commerce, ease suffering, and reduce burdens. Without it, the debtor is forced to transfer money owed to the creditor to his/her country. This is an additional cost that should be removed. Muslim jurists have discussed the ruling of the issue and have permitted its practice in the absence of any benefit required in the contract, or if the bill of exchange benefits both the lender and borrower, or in cases of necessity, or if the benefit is for the borrower alone, but they differed in its judgment in the case of a loan contract. After presenting the views of the jurists on this issue and their respective arguments, we have preferred the view permitting benefit from the bill of exchange in loans provided that there is no harm to the debtor or borrower. We assert that all bank transfer processes and remittance are forms of bill of exchange in Islamic jurisprudence, with slight differences between them. This research has adopted the comparative analytical method based on the study of texts and their analysis and discussion, so as to highlight various forms of bill of exchange and legal applications in the light of the views of Muslim jurists and their respective evidence. Key words: Bill of Exchange, Debt, Remittance, Bank Transfers, Legal Application.